Empowering citizens in conservation of family medicinal plants through processing rosella flowers into tea - Mentari, Agustina Puspa; Al Mubarokah, Assaniyah Alfani; Azzahra, Afra Nabila; Nur'aini, Annisa Itsna; Sagita, Desky Arma; Jumiyati, Fitri; Amalia, Melita Khusnul; Mumayizah, M.; Mugiyo, Surya Agung Wibowo; Marwantoro, Teguh; Hasanah, Tita Roliatun; Sari, Yulia Permata; Zain, Zarra Faizah; Khoerunisya, Alfida Neelam Kurnia; Riatmo, Pawit; Salimi, Moh (Universitas Pendidikan Indonesia, 2023)
The quality of health in Indonesia is included in the low category compared to other countries. Based on the results of the GHSI (Global Health Security Index) report, the average global health score is 38.9 points out of a score of 100 points. Meanwhile, Indonesia's global health security index ranks 13th compared to other G20 countries. One of the factors causing a country's low quality of health is caused by the level of a country's economy. This program aims to empower people in the fields of health, economy, and human resources by conserving family medicinal plants from roselle flowers that are processed into tea. The method used in this program is participatory, where environmental scanning is integral to empowering communities through building self-reliance with the power of resources and products. Program results are achieved from the fulfillment of success indicators prepared based on the objectives of the implementation of the program. There are nine main points in the indicators of success that can be achieved. In conclusion, the community empowerment program in Jatimalang Village, Klirong District, Kebumen Regency, has been built from the fulfillment of village-based SDGs and the awareness of the superiority of natural potential owned.